In-situ-Hybridisierung in der klinischen Pathologie: Bedeutung der Polysomie 17 für die HER2-Bestimmung und genetische Tumorheterogenität im Mammakarzinom - Gaiser, Timo; Rüschoff, Jan Hendrik; Moll, Roland (Der Pathologe, 2012)
The introduction of total genome sequencing led to the confirmation that tumors show substantial genetic heterogeneity. This phenomenon, which describes the presence of different genetic cell clones within a tumor also complicates the diagnostics of HER2. This article gives a review of new knowledge on polysomy 17 and genetic tumor heterogeneity in connection with HER2 determination of breast cancer.